The effectiveness of prevention and rehabillitation programme run by punarjivan kendra on drug addicts. - Limbu, Munna Tumbrok (2002)
ABSTRACT: The abuse of drug is an international problem, which affects almost every country in the world, both developed and developing. Current evidence from around the world reveals a continuing upward trend in the misuse of psychoactive drugs. Nepal is also caught in the web of the drug addiction problem, Especially, younger generation are becoming of HIV/AIDS through drug abuse has added new dimension to the drug addiction problem. Thus various counter-measures have been taken singly or jointly by government, NGOs and INGOs in order to combat with drug addiction problem. It is recognized that NGOs can play vital role in the reduction of demand to illicit drug and drug use. The study entitled "The Effectiveness of Prevention and Rehabilitation Program Run by Punarjivan Kendra on Drug Addicts" was conducted in Dharan Muncipality. It was iontended to identify the causes of drug addiction in Dharan and to explore the effectiveness of prevention and rehabilitation programme run by Punarjivan Kendra on drug addicts of Dharan municipality. To achieve the goals of this study, descriptive research design has been adopted. Primary and secondary source of data have been equally used. The study comprised 76 samples of outreach service holder (current drug addicts for the study which represent 17 per cent of the total outreach service holder at the time of the study. These sample population has been contacted through purposive sampling technique. Two types of instruments were applied to collect information related to the objectives of the study. Quantitative information was obtained from individual questionnaire administered to outreach service holder and qualitative information was obtained through case study and key informants interviews. For data analysis simple statistical methods like frequency count and percentage distribution were applied. After collecting the data, It was found that the major causes of drug addiction in Dharan is due to the socio-cultural and psychological factors. Rai-Limbu were the most drug affected ethnic/caste group than other ethnic/caste group in Dharan. Unmarried and unemployed young people are amongst ther durg addict population. Majority of drug addicts belonged to the age group (15-24) years. Besides, peer influence were the major reason for drug introduction. Furthermore, multiple drug use is most common practice among drug addicts. Synthetic drug has dominated the drug scene of Dharan. Nitrazepam, phencidy. and tedigesic are the most used drug amongst drug addicts of Dharan. Though, the drug addicts are not confirmed to only one mode of drug administration, injecting drug is most common amongst drug addicts. It is found that 31.67 per cent share common needle, which shows the likelihood of the transmission of HIV/AIDS still persists amongst IDUs. Punarjivan Kendra (PJK) is the only NGO in Dharan that works for prevention, treatment and rehabilitation for drug addicts. Prevention programme is trargeted at both, drug, users as well as at risk group and community people. At risk groups such as students are given drug education/information at their school. Parents meetings are held and teachers are provided training because they can reach young potential users more effectively and efficiently. Overall, the efforts of prevention programme is to raise mass awareness about ill-effects and social consciousness regarding the hazards of drug abuse in the society. In other aspects of prevention programme, It is directed at the drug addicts in order to reduce drug related harm. Outreach service are provided to them (drug addicts) in which various services such as primary health care, counseling, education on safer sex, safe injection behavior, HIV/AIDS, STD are given, and preventative materials such as condom, sterilized water, bleach are distributed. It has provided treatment and rehabilitation services and follow up services to the addicts, in order to reintegrate into society. As far as drug detoxification is concerned, its achievement is 100 per cent but it has rehabilitated 44 per cent drug addict at the maximum which is satisfactory because for successful rehabilitation, not only the role of personnel at the center is important but the role of family, relatives and society is also indispensible. The case study also indicates that treatment attempts is successful among the drug users who voluntarily go for admission at the center. Overall, prevention and rehabilitation programme run by PJK for drug addicts in Dharan should be appreciated in light of the limited resources and fund available at its disposal.